EFFECTS OF E-LEARNING IN BASIC TRANSLATION COURSE FOR THE ENGLISH PRE-SERVICE TEACHERS (Proceedings of the International Conference on Future of Education, 2018)
This framework of the study is a quasi-experimental research. The purposes of this study were to develop the-Learning lesson, to compare students’ translation learning ability before and after using the e-Learning lesson and to study the satisfaction of the English pre-service students in Basic Translation Course. The participants were 48 of English sophomore students, Faculty of Education, Suratthani Rajabhat University in the second semester of the 2017 academic year. The instruments employed in the experimental comprise of e-Learning lesson in Basic Translation Course, the test of translation learning used as a pre-test and post-test and the satisfaction questionnaire. The data were statistically analyzed by percentage, mean, standard deviation and t-test for dependent. The research findings indicated that the efficiency of the-Learning lesson in Basic Translation was at 75.12/77.86. The students’ achievement after learning by using the e-Learning lesson in Basic Translation Course was significantly higher than before at the .05 level. The satisfaction of the students on the e-Learning lesson in Basic Translation Course was at a high level.
Keywords: satisfaction; translation ability; e-Learning